DEVELOPMENT OF ANDROID-BASED EDUCATIONAL GAME MEDIA ON EARTH AND THE SOLAR SYSTEM TO IMPROVE GRADE VII STUDENTS’ LEARNING - Rahmawati Yanita Sari; Andriana Putri Kurniawati; Atika Anggraini (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2026)
This research aims to develop Android-based educational game media on Earth and Solar System materials to improve the learning outcomes of grade VII students at MTsN 1 Kediri City. The background of this research is the lack of use of interesting and interactive learning media so that student learning outcomes are still low or have not reached the Learning Goal Achievement Criteria (KKTP). The method used is Research and Development (R&D) with a Four-D (4D) model which includes Define, Design, Develop, and Disseminate stages. Data was obtained through expert validation as well as students' Pretest and Posttest results, then analyzed using feasibility and effectiveness tests (normality, homogeneity, paired sample t-test, and N-gain tests). The results of the study showed that the developed media was very feasible with a percentage of assessment of material experts of 88.7%, media experts of 94.3%, and question experts of 90%. The effectiveness test showed an increase in learning outcomes with a sig. (2-tailed) value of 0.000 < 0.05 and an N-gain value of 0.5888 in the medium category. Thus, Android-based educational game media is declared feasible and effective enough to improve student learning outcomes.